muntasir muntasir dkk Penyuluhan Dan Penguatan Karakter Perilaku Kebersihan Dan Kesehatan Bagi Pekerja Sektor Informal Untuk Tetap Produktif Pada Saat Situasi Dan Kondisi Pandemi Covid 2019 Di Lasiana Kupang NTT - Muntasir, Muntasir; Roga, Anderias Umbu; Weraman, Pius; Kuswara, Ketut Mahendra; Manongga, SP.; Ratu, Jacob M.; Manalu, Teacher (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Activities of implementing research results for many audiences have been carried out in the form of socialization of the delivery of scientific knowledge material in the form of counseling and strengthening hygiene and health behavior for informal sector workers in order to remain productive during the situation and conditions of the 2019 Covid pandemic in Lasiana Kupang Ntt which have been carried out efficiently and carefully. . Community service method with the following stages: 1) planning and design of activities; 2) supply of materials as needed; 3) pre-implementation preparation and implementation of activities; 4) delivery of counseling materials and socialization of strengthening the character of hygiene and health behavior for informal sector workers to remain productive during the situation and conditions of the 2019 Covid pandemic in Lasiana, Kupang Ntt; 5) questions and answers and brainstorming and suggestions from implementers and target partners; 6) Field monitoring by monitoring supervisor; 7) results of evaluation from community partnership activities and 8) the final report of the activity. The output of this activity is knowledge and understanding for informal sector workers affected by Covid 2019, especially construction workers and temporary workers in Lasiana, Kupang city, to always carry out healthy patterns and behavior, especially clean and healthy living habits and provide humanitarian assistance in form of food needs, masks and hand sanitizer.